Larangan Bertempat Tingal Di Wilayah Non Muslim (Studi Takhrij dan Pemahaman Hadis) - Agusri Fauzan (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Modern life which is characterized by globalization makes the flow of human movement from one place to another easier, more effective, and efficient. The world is becoming smaller and it is easier to enter any area in the corner of the earth. Likewise, the choices that arise for humans to live, work, do business, study, travel and so on. Of all regions on this earth, not all of them are inhabited by Muslim-majority communities, but more non-Muslim-majority communities. So this study aims to see the status and understanding of the prophet's hadith about the prohibition of living in non-Muslim communities in the present context. This paper is the result of a literature study, which is the result of tracking several literatures related to the themes discussed. The method used in this paper is a qualitative research method that is descriptive and interpretive through a historical approach. The results of the study conclude that this hadith is ahad and is valid and can be used as evidence. The understanding of this hadith contains a prohibition for Muslims to live in non-Muslim countries due to war between Muslims and non-Muslim countries, great difficulties that cause a Muslim to be unable to fulfill his obligations, and affect a lifestyle that causes a Muslim to have no difference with other people. non-muslim. This prohibition does not apply if the non-Muslim country is safe, there is no difficulty in worshiping and fulfilling obligations as a Muslim, and can show the identity and lifestyle of a Muslim.